(untitled) (Journal of Global Humanities and Social Sciences, 2024)
Shen Congwen’s works are famous for his unique depiction of landscapes, in which the delicate descriptions of natural and humanistic landscapes not only beautify the background of the story but also profoundly express the emotional and psychological state of the characters, as well as reflect the rich social and cultural background. This paper discusses the characteristics of landscape narration in Shen Congwen’s novels and its significance in modern literature. These creative techniques of Shen Congwen not only have an important influence on the landscape description in modern literature but also provide a deep insight into the cultural perception of society.